Estudo da dinâmica de crescimento filamentar na comutação resistiva em filmes finos de ZnFe204 - Evaristo, Diego da Silva (2019)
In this work we study the influence of the compliance current (ICC), thickness (deposition time 1, 2, 3 and 4h) and the metal used as electrode in the dynamics of filamentous growth in the ZnFe2O4 (ZFO) zinc ferrite resistive switching. The films were obtained by Sputtering technique on glass substrates fixing the lower electrode and varying the metal used as the upper electrode. The metals Ag, Cr and Al used as electrodes were grown symmetrically (Metal 1 - ZFO - Metal 1) and non - symmetrical (Metal 1 - ZFO - Metal 2) to perform electrical measurements (I x V curves) used for switching observation. Circular dots with a diameter of 1mm used with upper contacts were deposited with a shade mask by Sputtering. The properties of the films studied here were characterized by x-ray diffraction measurements and I x V curve measurements. It was possible to observe the formation of the phase, to estimate the growth rate and thickness of the films, to evaluate the resistance electrodes and film as well as resistive switching. We verified that the metals used as electrodes grow with a preferential direction even over the (amorphous) glass, the ZFO phase was observed at a temperature of 400 oC with more than 2h of deposition. ZFO films as prepared have a resistance greater than 100 M. The results demonstrate the influence of compliance current (ICC), thickness and metal contacts on the growth dynamics of conductive filaments. The switching measures for the devices with asymmetric electrodes demonstrate the characteristic of bipolar switching, however, we verified that for low compliance current of the device Cr/ZFO(4h)/Ag demonstrated the switching mode threshold. We verified the formation of the ohmic space at the junction between the metallic electrode and the insulation layer, proved by means of the adjustments in the linear relation I x V of each resistive state. All devices evaluated demonstrate good resistive switching characteristics with good stability, repeatability and on/off rate.